A clinical study on preserving the vitality of dental pulp affected by jawbone cysts - WANG Xinbin; LI Yuanyuan; ZHU Hongjie; CHEN Jiu; WANG Haojun; LANG Lin (Kouqiang hemian waike zazhi)
[Objective:] To evaluate the impact of jaw cystic lesions on dental pulp tissue, providing a basis for the effective preservation of the anatomical structure and function of teeth. [Methods:] Between August 2021 and December 2022, a total of 51 teeth with live pulp and cystic lesions affecting the roots were studied at our institution. These teeth were categorized based on the extent of cystic involvement in the root region: 27 teeth were categorized as apically involved (apical group), while 24 teeth were not apically involved (non-apical group). Preoperative and postoperative pulp vitality values were measured and subjected to t-test analysis. Additionally, 43 teeth underwent bone grafting in the surgical area (bone grafting group), whereas 8 teeth did not receive bone grafting (non-bone grafting group). Changes in pulp vitality before and 3 months after surgery were recorded and analyzed using t-tests, with a significance level set at P<0.05. [Results:] There were no statistically significant differences in pulp vitality changes between the apical and non-apical groups (P>0.05). Similarly, no statistically significant differences were observed in pulp vitality changes between the bone grafting and non-bone grafting groups (P>0.05). [Conclusion:] Vital pulp in teeth with apical involvement due to jaw cystic lesions can be preserved; bone grafting after jaw cyst surgery does not affect the pulp vitality of the involved teeth.